Regional propolis extracts suppress Fusarium fujikuroi and boost rice seedling growth and response against Bakanae disease - Zeinab A. Kalboush; Yasser S.A. Mazrou; Sara H. Elzan; Eatemad M. Zanaty; Alyaa A.A. Gazzy; Marwa B.M. Gomaa; Abeer H. Makhlouf; Yasser Nehela (Plant Stress)
Bakanae, caused by Fusarium fujikuroi, is a serious seed-borne disease affecting rice production worldwide. Herein, we investigated the potential of propolis, a natural honeybee product, collected from three geographic locations in Egypt: North (Menofia), Middle (Cairo), and South (Sohag), and extracted with four different solvents (ethanol, olive oil, hexane, and water) as a sustainable eco-friendly alternative to control the Bakanae disease in rice. In vitro experiments showed that propolis extracts exhibited antifungal activity against F. fujikuroi and significantly suppressed its mycelial growth and sporulation. The antifungal activity of propolis extracts was associated with its chemical composition which varied depending on geographical origin, and the extraction solvents. Moreover, SEM-based analysis revealed that ethanolic extract of northern propolis prominently altered the microconidia morphology of F fujikuroi, which shrunken and seemed to lose their viability. These findings were further confirmed in vivo under greenhouse conditions. Soaking F fujikuroi-inoculated rice seeds in 1000 ppm of propolis extract significantly reduced the bakanae disease incidence, and disease severity index compared to mock-treated controls. Although infection with F fujikuroi induced the accumulation of H2O2, the application of propolis extracts alleviated oxidative stress and significantly reduced the H2O2 levels within infected rice seedlings. Moreover, propolis extracts enhanced the profile of enzymatic antioxidants (guaiacol-dependent peroxidase [POX] and polyphenol oxidase [PPO]) in F. fujikuroi-infected rice seedlings. Finally, Propolis extracts-treated rice seedlings exhibited higher transcript levels of three PTI-marker genes including nonexpressor of pathogenesis-related genes 1 (OsNPR1), WRKY transcription factor 21(OsWRKY21), and phenylalanine ammonia-lyase (OsPAL1), which are associated with systemic acquired resistance (SAR) and crucial for the plant's defense response against pathogens. Collectively, these findings suggest that propolis might be a promising sustainable, eco-friendly alternative to control bakanae disease and other fungal seed-borne phytopathogens due to its antifungal properties and ability to induce a complex multilayered defense system within infected plants.